Effects of childhood bronchiectasis on cardiac functions - AKALIN, FİGEN (My University, 2003)
BACKGROUND: Bronchiectasis is still a widespread disease in developing countries. It is an important cause of mortality and morbidity. The information on cardiac involvement in bronchiectasis is limited. However, cor pulmonale is common in patients with chronic lung disease, such as cystic fibrosis. METHODS: We utilized echocardiography and exercise tests, along with clinical scoring, chest radiograph scoring, and pulmonary function tests in 21 patients to determine whether detectable changes in cardiac functions were present, and the nature of their relationship to the underlying disease severity. RESULTS: The ventricular systolic functions were preserved in all patients. Some of the patients had changes in left ventricular diastolic function indices, characterized by abnormal Ewave/Awave (E/A) ratios or isovolumetric relaxation time values. Isovolumetric relaxation time but not E/A ratios was found to have a significant negative correlation with the clinical score. In addition, exercise capacity was decreased in bronchiectatic children. Most of the patients stopped the exercise test due to exhaustion before reaching maximum heart rate. CONCLUSION: Left ventricular diastolic functions are affected in bronchiectasis, and the performance of patients is dependent on their pulmonary status. This is the first study demonstrating the cardiac effects of bronchiectasis according to our survey of the published literature.
Keywords: Female; Humans; Adolescent; Male; Child; Heart; Respiratory Function Tests; Bronchiectasis; Diastole; Systole; Exercise Test; Ventricular Function, Left